Comparing copromicroscopy to intestinal scraping to monitor red fox intestinal helminths with zoonotic and veterinary importance - Marchiori, Erica; Obber, Federica; Celva, Roberto; Marcer, Federica; Danesi, Patrizia; Maurizio, Anna; Cenni, Lucia; Massolo, Alessandro; Citterio, Carlo Vittorio; Cassini, Rudi (Frontiers in Veterinary Science, 2023)
The red fox acts as an epidemiological reservoir for several helminthic infections which are of interest for both public and veterinary health. Huge effort has been spent for the assessment of the sensitivity of coprological tests for the detection of Echinococcus multilocularis in this host, while less attention has been addressed to other helminthic species. This study aimed at assessing the performance of two copromicroscopic techniques in the detection and prevalence estimation of gastrointestinal helminths of the red fox. Helminths were isolated from the small intestines of 150 red foxes with a scraping, filtration and counting technique (SFCT) and morphologically identified. Rectal content was collected as well and submitted to two coproscopic techniques, i.e. a simple flotation (FT) and, only for Taenids, a method based on the concentration of eggs and identification with multiplex PCR (CMPCR). Using the results of SFCT as a reference standard, the sensitivity of copromicroscopic tests was assessed. Three species of nematodes (namely, Toxocara canis, Uncinaria stenocephala and Pterygodermatites sp.) and five species of cestodes (E. multilocularis, Taenia crassiceps, Taenia polycantha, Hydatigera taenieformis, Mesocestoides sp.) were retrieved with SFCT, and eggs referable to the same taxa were detected with fecal examination, except Pterygodermatites sp. and Mesocestoides sp. The sensitivity of FT was low for all taxa, ranging from 9.8 to 36.3%, with lower values for Taenids. Performance of CMPCR was slightly better for this group (23.5%) and the multiplex PCR on eggs was effective in the identification of Taenid species. Prevalence of the different helminthic infections appears underestimated also in other surveys when the copromicroscopic approach is used and compared with necroscopic findings, with the extent of such difference varying with taxon, and showing higher extent at higher prevalence levels, in particular for cestodes. Irregular dynamics of egg shedding and routinary deep freezing of red fox droppings, may account for a great part of negative results at copromicroscopy. Low sensitivity of copromicroscopic tests should be taken into account when using this approach for prevalence estimation in red fox populations and appropriate attention should be given to the definition of a correct sample size.